Surface Modification of Electrospun PVDF/PAN Nanofibrous Layers by Low Vacuum Plasma Treatment - Fatma Yalcinkaya; Baturalp Yalcinkaya; Adam Pazourek; Jana Mullerova; Martin Stuchlik; Jiri Maryska (International Journal of Polymer Science)
Nanofibres are very promising for water remediation due to their high porosity and small pore size. Mechanical properties of nanofibres restrict the application of pressure needed water treatments. Various PAN, PVDF, and PVDF/PAN nanofibre layers were produced, and mechanical properties were improved via a lamination process. Low vacuum plasma treatment was applied for the surface modification of nanofibres. Atmospheric air was used to improve hydrophilicity while sulphur hexafluoride gas was used to improve hydrophobicity of membranes. Hydrophilic membranes showed higher affinity to attach plasma particles compared to hydrophobic membranes.